2023
DOI: 10.3389/fnins.2023.1138952
|View full text |Cite
|
Sign up to set email alerts
|

Decreased gray matter volume in the right middle temporal gyrus associated with cognitive dysfunction in preeclampsia superimposed on chronic hypertension

Abstract: IntroductionThe effects of preeclampsia superimposed on chronic hypertension (CHTN-PE) on the structure and function of the human brain are mostly unknown. The purpose of this study was to examine altered gray matter volume (GMV) and its correlation with cognitive function in pregnant healthy women, healthy non-pregnant individuals, and CHTN-PE patients.MethodsTwenty-five CHTN-PE patients, thirty-five pregnant healthy controls (PHC) and thirty-five non-pregnant healthy controls (NPHC) were included in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This is consistent with previous studies and may be related to the damage or death of basal ganglia nerve cells caused by insufficient blood supply, oxidative stress and inflammation caused by hypertension. 25,26 In addition, previous studies have found that both the volume of BG are found to decrease with age in healthy volunteers. 27,28 In this study, we found that this phenomenon is not only in healthy people, but also in patients with high blood pressure.…”
Section: Discussionmentioning
confidence: 93%
“…This is consistent with previous studies and may be related to the damage or death of basal ganglia nerve cells caused by insufficient blood supply, oxidative stress and inflammation caused by hypertension. 25,26 In addition, previous studies have found that both the volume of BG are found to decrease with age in healthy volunteers. 27,28 In this study, we found that this phenomenon is not only in healthy people, but also in patients with high blood pressure.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, in comparison to the Non preeclamptic group, the Grey Matter Volume in a cluster of the right middle temporal gyrus (MTG) was significantly reduced in the Preeclamptic groups. 14 The extent to which autonomic dysfunction leads to brain alterations following pregnancy is yet unknown. 2020), it was shown that pregnant women who had both gestational diabetes mellitus (GDM) and autonomic dysfunction had a notably greater occurrence of preeclampsia compared to those who had just one of these conditions.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%